국내 헬리콥터 시뮬레이터 현황 및 필요성 검토 - 조영진; Cho, Young-jin (한국항공운항학회지, 2017)
A flight simulator is an instrument which lets pilots attain proficiency of handling various emergency situations, and the sense of flying. In this thesis, current status of domestic simulators will be stated, and after showing the problems with the present management of these simulators, comparisons of how and what kind of facilities they are managed around the globe will be made. After comparing and analyzing the difference in the way the simulators are ran, measures of improvement in domestically appropriate simulators and increase of operating facilities will be drawn.